’n Omvattender aanbod van semantiese data in aanlyn woordeboeke - Gouws, Rufus H. (Lexikos, 2025)
A More Comprehensive Presentation of Semantic Data in Online Dictionaries. Meaning is the type of data most frequently needed by dictionary users. Due to space restrictions printed dictionaries can only offer a limited reflection of those aspects of meaning relevant to dictionary users. In determining features of meaning to be used in explanations of meaning, lexicographers are often guided by insights from older approaches in linguistics. Consequently, a strict division is often still maintained between linguistic and encyclopaedic data. Following an overview of some aspects of dictionary typology, dictionary structures and semantic data in printed dictionaries, this paper offers suggestions for the use of new types of dictionary structures to ensure a more comprehensive presentation of semantic data in online monolingual dictionaries. In the different subcomments on semantics in dictionary articles, provision is made for a horizontal ordering of different compartments to accommodate different types of data. More space is allocated to semantic data and also to data that fall beyond the scope of traditional dictionary entries. A stronger focus is placed on semantic relations and ways in which this type of semantic guidance could be accommodated in the comment on semantics. New types of integrated microstructures are suggested to make data accessible for target users, and suggestions are also made for the retrieval of information from dictionary-external sources. Semantic data should be presented as good and as comprehensive as possible in monolingual dictionaries. Keywords: comment on semantics, compartments, delayed integrated microstructure, integrated microstructure, levels, multi-phased integrated microstructure, parallel integrated microstructure, paraphrase of meaning, search tunnel, search universe, semantic data, shaft structure, subcomment on semantics